Relaxation properties of defect complexes in SrCI₂-TI+ crystals - Kachan, S.I.; Salapak, V.M.; Chornyi, Z.P.; Pirko, I.B.; Kushnir, T.M. (Functional Materials, 2004)
Two maxima are observed in the thermograms of of the thermostimulated depolarization currents of SrCI₂-TI+ crystals have been observed: a low-temperature one (Tm = 107 K, £m = 0.24 eV), caused by the reorientation of Tl+Va+ dipoles, and high-temperature one (Tm = 215 K, £m = 0.46 eV) related to thermal dissociation thereof. TI+Va+-dipoles possess C3V symmetry, that results in splitting of the absorption А-band (1S033 transition) into two components with maxima at 234 and 247 nm. At low-temperature irradiation (T < 140 K), TI+VD+-dipole concentration (at the stage of a crystal coloring saturation) is decreased by 15-20 % as a consequence of charge carrier capture by TI+-ions.